Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing


  • 3 years ago

Solve the following for x: 3 – (x +(-4)) = 2x – 6 + 5x Explain in as much detail as possible.

  • This Question is Closed
  1. across
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    You have:\[3-(x+(-4))=2x-6+5x.\]Simplify the left hand side by expanding the parentheses:\[3-x-(-4)=2x-6+5x,\\3-x+4=2x-6+5x.\]Combine like terms in both the left and right hand sides:\[7-x=7x-6.\]Solve for \(x\):\[13=8x,\\x=?\]

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy